An Analysis of The Impact of Daily Activity Reporting Via the Si Tamppan Application on Employee Productivity at The Wonogiri Regency Communication and Informatics Office - Endri Sulistyoningsih; Sri Wijiastuti; Zandra Dwanita Widodo (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This research aims to analyze the effect of daily activity reporting through the SI TAMPPAN application on employee productivity at the Department of Communication and Informatics of Wonogiri Regency. The implementation of the SI TAMPPAN application is part of the Wonogiri Regency Government’s initiative to enhance the effectiveness of employee performance management through systematic and integrated daily activity recording. This research adopts a descriptive qualitative approach. Data were collected through in-depth interviews with employees who actively use the SI TAMPPAN application, direct observation of the daily activity input process, and the review of relevant supporting documents. Data analysis was conducted using NVivo software through coding, thematic categorization, and mapping of relationships among concepts to obtain a comprehensive understanding of how the application influences employee productivity. The findings indicate that daily activity reporting via the SI TAMPPAN application has a positive impact on employee productivity. This impact is reflected in improved discipline in managing working time, clearer work targets and task completion, and increased employee awareness of job responsibilities that must align with Individual Performance Indicators (IKI). Furthermore, the SI TAMPPAN application functions as a monitoring tool that encourages employees to work in a more structured and measurable manner. Nevertheless, this study also identifies technical constraints and variations in employee compliance levels in using the application, which require continuous evaluation and ongoing assistance. In conclusion, daily activity reporting through the SI TAMPPAN application contributes to supporting improvements in employee productivity. However, further refinement in technical aspects and implementation strategies is necessary to ensure that its benefits can be optimally realized.